Disturbance Observer-Based Control to Guarantee a Sliding Mode Without Sliding Mode Control - Keonwoo Lee; Jaejun Cha; Seungkyu Park (IEEE Access, 2023)
This paper presents a novel disturbance observer (DOB)-based control method to prevent the deterioration of transient response due to disturbances. The proposed method uses sliding mode dynamics without a sliding mode control (SMC) structure and does not require an upper bound of disturbance (UBD), which is needed for SMC. The proposed DOB focuses on maintaining sliding mode dynamics while minimizing the estimation error. The sliding function and disturbance estimation error are considered simultaneously in a Lyapunov candidate function. By modifying the dynamics of the auxiliary variable in the DOB model, the proposed DOB system ensures that the states remain close to the sliding surface and preserve the desired control system characteristics. In contrast, existing DOB models focus only on disturbance estimation and suffer from control performance deterioration during transient estimation time. The proposed DOB-based control method adopts an integral sliding mode and shows better ability to maintain the sliding mode than integral SMC (ISMC).